Testing the phylogenetic utility of MCM7 in the Ascomycota - Huzefa Raja; Conrad L. Schoch; Vincent Hustad; Carol Shearer; Andrew Miller (MycoKeys, 2011)
The Ascomycota are a group of filamentous fungi that occur as saprobes, pathogens and symbionts of immense industrial, medical, ecological, and economical importance. The search for new markers appropriate for molecular phylogenetic analysis of Ascomycota remains a challenging problem. In this study, we explore the phylogenetic utility of a single copy protein-coding gene, MCM7; newly recognized as useful for inferring phylogenetic relationships among the major classes of the Ascomycota. Our specific goals were to; 1) test the phylogenetic utility of MCM7 for estimating phylogenies at various taxonomic ranks (class and below) with an emphasis on non-lichenized ascomycetes; and, 2) compare the congruence, robustness and resolving power of MCM7-based phylogenies with that of nuclear large subunit 28S rDNA (LSU)-based phylogenies for the same taxon set. A dataset of sequence data for MCM7 as well as LSU was assembled for 80 species belonging to 63 genera of lichenized or non-lichenized ascomycetes in the classes Dothideomycetes, Eurotiomycetes, Geoglossomycetes, Lecanoromycetes, Leotiomycetes, and Sordariomycetes. We obtained 99 new sequences of which 65 are MCM7 and 34 are LSU. Maximum-Likelihood and Bayesian analyses were performed using single as well as combined gene datasets and partitions. We also assessed substitution saturation for the MCM7 gene. Results indicate that MCM7 can be used successfully for determining phylogenetic relationships of non-lichenized ascomycetes and provided good resolution and support at half the cost compared to LSU. Phylogenetic informativeness profiles using PhyDesign tool shows MCM7 was a higher phylogenetic informative gene than LSU. The MCM7 gene is also a valuable phylogenetic marker for both lower as well as higher level phylogenetic analyses within the non-lichenized Ascomycota, especially when used in combination with the LSU gene. We found that although the third codon position of MCM7 is saturated, it was better to analyze the dataset with all codon positions included. Phylogenetic performance of MCM7 with and without the third codon position is discussed.